'Let us Sin with Salvin': Architecture and Authority at the Tower of London, 1896–1905. (17th November 2017) - Inglesby, Roisin
Abstract: The Tower of London is one of the most famous sites in the world, yet its recent architectural history has been almost entirely overlooked. This article represents the first attempt to explore the architectural approach taken by the Tower authorities at the turn of the twentieth century. It analyses the on-going programme of restoration undertaken by the Office of Works during this period in the context of the Tower's singular status as military garrison, historic monument and preeminent tourist attraction, and it considers the Office's stance in relation to increasing public and parliamentary interest in the preservation and restoration of historic buildings. Historic Royal Palaces' collection of architectural drawings offers an unexplored insight into the activities of the Office of Works during this time. Through a close reading of these drawings I show that, contrary to what has previously been supposed, the Office's interventions continued well past the radical restorations of the 1880s and into the twentieth century, as they sought to control the historical narrative of the site through its architecture.